(untitled) (Филолошки студии, 2019)
The Slavic languages had been developed from a general protolanguage and still have numerous general features, but today, after eleven centuries they are independent languages, formed under different influences of the neighbouring countries, historic conditions etc. Generally, the term Pan –Slavic lexical fund is still in use, but practically, even within it can be found differences in meaning. The homonymy and the polysemy can present a problem even in the framework of one language, while on Pan-Slavic level such occurrences are even more numerous and the problems related to them are rather bigger. In the article, using examples from different Slavic languages, an attempt is made to analyze certain types of homonymy and polysemy which are found in current lexica, to determine the ways of their creation and to notify the possible ways of decreasing or avoiding the problems in this field.